Analisis Yuridis Penanganan Pasien Gawat Darurat di Rumah Sakit Kurnia Cilegon Berdasarkan Undang-Undang Kesehatan - Wawan Ari Kuncoro; Agus Ariadi (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
Emergency services in the Emergency Installation must prioritize the safety of patients' lives over administrative or financing interests. The birth of Law Number 17 of 2023 concerning Health has further strengthened the doctrine of anti-dumping or the prohibition of refusal of patients in health facilities. However, in today's society, there is a strong misconception that the restriction of emergency handling claims is a unilateral regulation issued by the Health Social Security Organizing Agency. This study aims to analyze the conformity of the Triage Operational Procedure Standard at Kurnia Cilegon Hospital with Law No. 17 of 2023 and to straighten out the juridical understanding of the origins of the emergency criteria regulation. The research method used is normative juridical with a statute approach through the analysis of legal documents. The results showed that the Standard Patient Triage Operating Procedures at Kurnia Cilegon Hospital has clinically adopted the Australasian Triage Scale. The main obstacle to the implementation of this rule stems from the disparity in the regulation of emergency criteria set by the Ministry with the absolute norm of life protection in the Health Law, the limitation of medical facilities, and the hospital's anxiety about the risk of unclaimed medical service costs. The public's lack of understanding regarding the restriction of emergency criteria accused of the Health Social Security Administration Agency needs to be straightened out, because the Health Social Security Administration Agency acts as the implementing agency for operational guarantees that comply with the regulatory order of the Ministry of Health.